1989
DOI: 10.1093/geronj/44.4.m112
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Falls in a Community-Based Prospective Study of People 70 Years and Older

Abstract: We investigated factors associated with falls in a community-based prospective study of 761 subjects 70 years and older. The group experienced 507 falls during the year of monitoring. On entry to the study a number of variables had been assessed in each subject. Variables associated with an increased risk of falling differed in men and women. In men, decreased levels of physical activity, stroke, arthritis of the knees, impairment of gait, and increased body sway were associated with an increased risk of falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
559
13
16

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 884 publications
(633 citation statements)
references
References 0 publications
37
559
13
16
Order By: Relevance
“…It is known that most falls occur when the body is in motion and not during static tasks (Maki & Mcllroy, 1996;Campbell, Borrie, & Spears, 1989). For example, Maki and Mcllroy, (1996) indicated that 54% of falls are due to a slip, trip, overstepping, or a BOS problem during weight transfer.…”
Section: Postural Control During Locomotionmentioning
confidence: 99%
“…It is known that most falls occur when the body is in motion and not during static tasks (Maki & Mcllroy, 1996;Campbell, Borrie, & Spears, 1989). For example, Maki and Mcllroy, (1996) indicated that 54% of falls are due to a slip, trip, overstepping, or a BOS problem during weight transfer.…”
Section: Postural Control During Locomotionmentioning
confidence: 99%
“…This underlines the importance for public health-care systems to better understand age-related syndromes and diseases, such as sarcopenia. This condition is characterized by a progressive loss of skeletal muscle mass and its action generating capacity-also termed muscle function-and implies a risk of adverse outcomes such as fall-related injuries and impaired quality of life (Campbell et al 1989;Cruz-Jentoft et al 2010;Rizzoli et al 2013). In addition, it is estimated that the prevalence of sarcopenia is approximately 1-33 % in the community (both genders combined) and that this prevalence increases in older populations (Cruz-Jentoft et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors associated with falls among communitydwelling elderly persons 2,3) include muscle weakness, use of certain medications, cognitive impairment, depression, and a history of previous falls [4][5][6][7] . Although falls often have a multi factorial etiology, most falls occur while walking 8) , and it is not surprising that gait impairment is also associated with increased risk of falls 9,10) . Gait dysfunction is a factor that makes daily living activities difficult and is a cause of serious functional disorders 11) .…”
Section: Introductionmentioning
confidence: 99%